2020
DOI: 10.3389/fphy.2020.00082
|View full text |Cite
|
Sign up to set email alerts
|

Normal Aging: Alterations in Scalp EEG Using Broadband and Band-Resolved Topographic Maps

Abstract: Given the majority of age-related diseases have been described as disconnection syndromes, understanding the functional connections of normal aging is of considerable importance. Here, an EEG-based scalp level analysis has been performed to identify the alterations in the synchronized brain regions in aged, compared to young persons. Two groups, aged and young subjects were studied, each consisting of 18 participants. First, conventionally extracted broadband topographic maps, also called microstate maps, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Indeed, spatial fluctuations and temporal modulations of alpha power have been linked to the emergence and persistence of specific microstates (Milz et al 2017 ; Croce et al 2020 ). Nevertheless, recent studies raised the question about whether the broad-band activity should be spectrally differentiated in order to identify and describe spatio-temporally overlapping spectral patterns (Javed et al 2019 , 2020 ). A recent study in adults found that during NREM sleep low frequencies dominated in all microstates, whereas the EEG power for high frequencies was higher during wakefulness (Brechet et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, spatial fluctuations and temporal modulations of alpha power have been linked to the emergence and persistence of specific microstates (Milz et al 2017 ; Croce et al 2020 ). Nevertheless, recent studies raised the question about whether the broad-band activity should be spectrally differentiated in order to identify and describe spatio-temporally overlapping spectral patterns (Javed et al 2019 , 2020 ). A recent study in adults found that during NREM sleep low frequencies dominated in all microstates, whereas the EEG power for high frequencies was higher during wakefulness (Brechet et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…An EEG study reported increased beta oscillations indicating greater GABAergic inhibitory activity within motor cortices of older than younger adults 19 . On the contrary, whole-brain age-related changes have mainly been reported in resting-state neuroimaging studies 8 , 13 , 17 , 18 , 20 22 . A resting-state fMRI study reported weakened within-network functional connectivity (FC), reduced system segregation, and lowered local efficiency in all primary sensory and cognitive networks 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Resting-state MEG studies have shown age-related spectral power decreases in low frequencies (e.g., delta) over most sensors covering the whole head 8 , 23 . Spectrally-resolved resting-state EEG topographic maps have revealed microstates from the delta to gamma bands showing significant age-related global differences in their spatial maps 20 . In these investigations, band-specific EEG/MEG power data 8 , 17 and fMRI amplitude data 10 , 17 were commonly used to evaluate regional changes (i.e., intra-region measures), while FC measures computed from either neurophysiological 16 or hemodynamic signals 13 , 24 , 25 evaluating dependence, interaction, and integration between regions are mainly used for cross-region and whole-brain changes (i.e., inter-region measures).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations